Anti-heavy-chain monoclonal antibodies directed to the acidic regions of the factor VIII molecule inhibit the binding of factor VIII to phospholipids and von Willebrand factor - Raut, Sanjeev; Villard, Sylvie; Grailly, Sabrina; Gilles, Jean-Guy G.; Granier, Claude; Saint-Remy, Jean-Marie R.; Barrowcliffe, Trevor W. (Thrombosis and Haemostasis, 2003)
Recent studies have shown that inhibitors develop against acidic regions of the FVIII molecule, which contain important functional sites. However, their mechanisms of inhibition are not well understood. In this study, two anti-human FVIII mouse monoclonal antibodies (MAbs), directed towards the exposed acidic regions of the FVIII molecule, were developed, characterised and their mechanisms of inhibition investigated. The two MAbs, F7B4 and F26F6, had inhibitory titres of 32 and 944 BU/mg respectively, had high affinities for the FVIII molecule (KD ~ nM range) and recognised sequences V357-F360 on the acidic a1 region and E724-L731 on the acidic a2 region of the FVIII heavy-chain (HC), respectively. F7B4 inhibited the rate of FXa generation by activated FVIII, whilst both antibodies inhibited FVIII activation by thrombin and blocked thrombin cleavage of FVIII. Furthermore, F7B4 and F26F6 inhibited FVIII binding to (a) phospholipids (IC50: 77 nM and 40 nM respectively), and (b) VWF (IC50: 93 nM and 267 nM respectively), despite both having HC specificity. Experiments with F(ab’)2 fragments confirmed the above findings. Taken together these data represent novel findings in that anti-acidic HC antibodies can inhibit FVIII function by a variety of mechanisms, in particular by interfering with the binding of FVIII to phospholipids & VWF.
Keywords: Factor VIII; monoclonal antibody; epitope; phospholipid; VWF